2016
DOI: 10.1128/genomea.01569-15
|View full text |Cite
|
Sign up to set email alerts
|

Two Complete Genome Sequences of Phasey Bean Mild Yellows Virus, a Novel Member of the Luteoviridae from Australia

Abstract: We present here the complete genome sequences of a novel polerovirus from Trifolium subterraneum (subterranean clover) and Cicer arietinum (chickpea) and compare these to a partial viral genome sequence obtained from Macroptilium lathyroides (phasey bean). We propose the name phasey bean mild yellows virus for this novel polerovirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It is nevertheless likely that this luteovirus-like sequence is from a virus that should be classified as belonging to the Polerovirus genus of the Luteoviridae . It is also noteworthy that ORF2 shares >80% nucleotide sequence identity with that of PBMYV, a novel polerovirus also isolated from phasey bean ( Macroptilium lathyroides ), a legume of the Fabaceae family [ 43 ]. However, ORF3 and ORF4 share <80% nucleotidic identity with the corresponding ORFs of PBMYV, suggests that the new virus could potentially be considered as either a new variant of PBMYV or a new Polerovirus species.…”
Section: Resultsmentioning
confidence: 99%
“…It is nevertheless likely that this luteovirus-like sequence is from a virus that should be classified as belonging to the Polerovirus genus of the Luteoviridae . It is also noteworthy that ORF2 shares >80% nucleotide sequence identity with that of PBMYV, a novel polerovirus also isolated from phasey bean ( Macroptilium lathyroides ), a legume of the Fabaceae family [ 43 ]. However, ORF3 and ORF4 share <80% nucleotidic identity with the corresponding ORFs of PBMYV, suggests that the new virus could potentially be considered as either a new variant of PBMYV or a new Polerovirus species.…”
Section: Resultsmentioning
confidence: 99%
“…The number of novel viruses discovered needed for a high-profile paper has increased by logarithms (Krishnamurthy et al, 2016;Shi et al, 2016). In the absence of particular phenotypic data or wet-lab viral characterization, many authors have turned to Genome Announcements, biorxiv, or simply uploading to Genbank with extra metadata, figuring that sequencing is the most likely future method of both detection and discovery (Debat, 2017;Greninger and DeRisi, 2015e,f;Karamendin et al, 2016;Sharman et al, 2016;Sparks et al, 2013). Given the glut of new viruses, expansion of sequencing, and the time it takes to publish, scientists may be more likely to align to your novel virus rather than read about it in a journal and decide to screen for it.…”
Section: Experimenting With Functionmentioning
confidence: 99%
“…In 1993, Horn et al first identified CpCDV, a virus of the family Geminiviridae, in India [ 25 ], and 19 types of CpCDV (CpCDV-a to s strains) have been reported. Then, CpCDV viruses have also been identified in the Middle East, Africa, South Africa, North Africa, South Asia, and the Arabian Peninsula [ 13 , 18 , 26 28 , 36 41 ]. Three CpCDV species of chickpea chlorotic dwarf Sudan virus (CCDSV), chickpea chlorotic dwarf Pakistan virus (CCDPV), and chickpea chlorotic dwarf Syria virus (CCDSV) can infest chickpea [ 6 ].…”
Section: Virus Characteristics Of Chickpeamentioning
confidence: 99%